Singly-Fed Large Frequency Ratio Composite Dielectric Resonator Antenna for sub-6 GHz and mm-Wave 5G Applications - Asadullah; Muhammad Umar Khan; Awab Muhammad; Mohammad S. Sharawi; Moath Alathbah (IEEE Access, 2024)
A dielectric resonator antenna (DRA) is proposed for dual-band resonance for the mid-band (sub-6 GHz) and the high-band (millimeter-wave) 5G applications. The proposed composite DRA consists of an annular dielectric radiator concentrically integrated with a high-permittivity cylindrical DRA to realize resonance at two distinct frequencies with large frequency ratio. The impact of composition of two distinct dielectric materials on the radiation in both bands is analyzed taking into account the effective permittivity of the composite structure. The composite DRA is excited with single Co-planar Waveguide (CPW). The proposed DRA offers resonance at 4.44 GHz in the mid-band and 27.92 GHz in the high-band. The radiation characteristics demonstrate broadside radiation pattern having 6.8 dBi and 4.3 dBi of gain in both bands respectively. The efficiency of the DRA is observed to be 87.1% and 84.71% in the sub-6 GHz and mm-wave bands, respectively. The radiation characteristics make the proposed composite DRA a potential design for numerous 5G applications.